RETRACTED: Molecular characterization of forest soil based Paenibacillus elgii and optimization of various culture conditions for its improved antimicrobial activity - Kumar, S. N.; Jacob, Jubi; Reshma, U. R.; Rajesh, R. O.; Kumar, B. S. D. (Frontiers in Microbiology, 2015)
Microorganisms have provided a bounty of bioactive secondary metabolites with very exciting biological activities such as antibacterial, antifungal antiviral, and anticancer, etc. The present study aims at the optimization of culture conditions for improved antimicrobial production of Paenibacillus elgii obtained from Wayanad forest of Western Ghats region of Kerala, India. A bacterial strain isolated from the Western Ghats forest soil of Wayanad, Kerala, India was identified as P. elgii by 16S rRNA gene sequencing. P. elgii recorded significant board spectrum activity against all human and plant pathogenic microorganism tested except Candida albicans. It has been well known that even minor variations in the fermentation medium may impact not only the quantity of desired bioactive metabolites but also the general metabolic profile of the producing microorganisms. Thus, further studies were carried out to assess the impact of medium components on the antimicrobial production of P. elgii and to optimize an ideal fermentation medium to maximize its antimicrobial production. Out of three media [nutrient broth (NA), Luria broth (LB) and Trypticase soy broth (TSB)] used for fermentation, TSB medium recorded significant activity. Glucose and meat peptone were identified as the best carbon and nitrogen sources, which significantly affected the antibiotic production when supplemented with TSB medium. Next the effect of various fermentation conditions such as temperature, pH and incubation time on the production of antimicrobial compounds was studied on TSB+glucose+meat peptone and an initial pH of 7 and a temperature of 30ºC for 3 days were found to be optimum for maximum antimicrobial production. The results indicate that medium composition in the fermentation media along with cultural parameters plays a vital role in the enhanced production of antimicrobial substances.